DNA meta‐barcoding using rbcL based mini‐barcode revealed presence of unspecified plant species in Ayurvedic polyherbal formulations. Issue 5 (1st February 2021) - Pandit, Ramesh; Travadi, Tasnim; Sharma, Sonal; Joshi, Chaitanya; Joshi, Madhvi
Abstract: Introduction: Ayurveda takes advantage of the beneficial properties of medicinal plants. High demands in combination with inadequate availability of botanicals and a lack of knowledge with respect to their precise identification lead to adulterations in herbal products. Identification becomes more difficult in complex herbal formulations. Four different polyherbal formulations have been analyzed for the present paper. The targeted plants have different pharmacological properties for various ailments. Objective: We aimed to examine the rbcL gene based plant DNA mini‐barcode to identify target and non‐target plants in polyherbal formulations by using high‐throughput next generation sequencing. Methods: Degenerate primers of the selected mini‐barcode region have been identified from the literature. A blend of 30 authentic medicinal plant species was used to examine the species resolution capacity of the mini‐barcode. DNA was isolated from herbal formulations, an amplicon library was prepared, and sequencing was performed on an IonS5 system. Data were analyzed using various bioinformatics tools. Results: Analysis of control pooled samples revealed the optimum resolving power of the DNA mini‐barcode. Data analysis of the commercial samples revealed that only one herbal formulation contained all plants and matched with listed contents. In two formulations, only 10 out of 21 and 11 out of 20 plants were detected, respectively. Additionally, several non‐listed plants were also detected in these formulations. Two formulations contained >20% reads assigned to non‐target plants. Overall, 21.98% of the reads were assigned to non‐target plants. Conclusion: The present study clearly demonstrated the successful application and potential of meta‐barcoding in the quality control of complex herbal matrices. The results strongly suggest that this approach can be used in pharmacovigilance of processed herbal products. Abstract : The paper highlighted the significance of metabarcoding in authenticating and in finding plant derived adulteration in polyherbal formulations. Metabarcoding using rbcL gene based plant DNA minibarcode clearly demonstrated the presence of non‐listed plant species in the four Ayurvedic polyherbal formulations. In addition, it is also suggested that multi‐loci metabarcoding can give better resolution in closely related species.